1994
DOI: 10.1111/j.1755-3768.1994.tb02731.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for an inflammatory response after extracapsular cataract extraction and posterior chamber IOL

Abstract: Risk factors for developing an inflammatory response after extracapsular cataract extraction with implantation of posterior chamber IOL have been studied. Out of 1154 cases included in the study, an inflammatory response was encountered in 63 eyes (5.5%). The inflammatory response was defined as increased cellular flare and/or as a fibrinous reaction during a follow-up of 4 months. Thirteen of the 63 eyes (20.6%) developed cellular precipitates, and posterior synechias were seen in 34 of these eyes (54.0%). Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 16 publications
0
20
2
Order By: Relevance
“…20 In PXF eyes undergoing extracapsular cataract extraction, evidence that supports the abnormal blood-aqueous barrier can be seen in several studies that show that postoperative pupillary fibrin membranes were more common in PXF eyes than in controls. [21][22][23] These same studies show an increase in inflammatory response in PXF eyes undergoing extracapsular cataract extraction. [21][22][23] When comparing complication rates between extracapsular cataract extraction and phacoemulsification in PXF eyes, several studies show a lower complication rate in those eyes undergoing phacoemulsification versus extracapsular cataract extraction.…”
Section: Pseudoexfoliation and Large-incision Extracapsular Cataract mentioning
confidence: 65%
See 1 more Smart Citation
“…20 In PXF eyes undergoing extracapsular cataract extraction, evidence that supports the abnormal blood-aqueous barrier can be seen in several studies that show that postoperative pupillary fibrin membranes were more common in PXF eyes than in controls. [21][22][23] These same studies show an increase in inflammatory response in PXF eyes undergoing extracapsular cataract extraction. [21][22][23] When comparing complication rates between extracapsular cataract extraction and phacoemulsification in PXF eyes, several studies show a lower complication rate in those eyes undergoing phacoemulsification versus extracapsular cataract extraction.…”
Section: Pseudoexfoliation and Large-incision Extracapsular Cataract mentioning
confidence: 65%
“…[21][22][23] These same studies show an increase in inflammatory response in PXF eyes undergoing extracapsular cataract extraction. [21][22][23] When comparing complication rates between extracapsular cataract extraction and phacoemulsification in PXF eyes, several studies show a lower complication rate in those eyes undergoing phacoemulsification versus extracapsular cataract extraction. 2,[24][25][26] However, phacoemulsification has been associated with an increased rate of vitreous loss and capsular and zonular tears in PXF eyes when compared to non-PXF eyes.…”
Section: Pseudoexfoliation and Large-incision Extracapsular Cataract mentioning
confidence: 65%
“…47,160 This includes more intense and/or prolonged postoperative inflammation, higher levels of aqueous flare, fibrinoid reaction, posterior synechias, IOL deposits, anterior capsule contraction, and macular edema. 161,162 Eyes with BAB alterations would be expected to carry a higher risk for postoperative macular edema. 163 Yet, PXF eyes without glaucoma are reported to have no increased risk for increased foveal thickness after uneventful phacoemulsification than control eyes, although those with glaucoma appear to be at increased risk.…”
Section: Intraoperative Subluxation Of Lens Fragments or Capsularmentioning
confidence: 99%
“…21 Drolsum et al emphasized that postoperative inflammation and a transitory fibrinoid reaction were more common in eyes with PEX after cataract surgery. 13,22 Ritch et al also found postoperative anterior chamber inflammation and recommended topical prednisolone acetate at three times weekly. 23 Increased levels of homocysteine (Hcy) in PEX and its relation with chronic inflammation have also been reported.…”
Section: Discussionmentioning
confidence: 95%